Surgical Single Stage Treatment for Obstructive Hypertrophic Cardiomyopathy and Aortic Arch Aneurysm - Margonato, Davide; Tolva, Valerio Stefano; Vaccari, Giuseppe; Bianchi, Paolo; Casana, Renato; Parati, Gianfranco; Ferrazzi, Paolo (AORTA, 2020)
Coexistence of obstructive hypertrophic cardiomyopathy and severe aortic pathology is extremely rare; nonetheless, the association between these two diseases is fascinating. Here we present a unique case report of a patient with obstructive hypertrophic cardiomyopathy and aortic arch aneurysm treated by a single surgical procedure.
Keywords: hypertrophic cardiomyopathy; aortic arch aneurysm; aortic replacement; aortic stent graft; myomectomy; myectomy